The Competency-based Curriculum of the Residency Program in Family Medicine at Faculdade de Medicina da Universidade de São Paulo - Machado, Lucas Bastos Marcondes (2018)
Objective: To present the steps taken to build a competency curriculum in family medicine residency program of the within the Medical School of the University of São Paulo; to describe fundamental characteristics and guidelines of the competency curriculum related to its three central attributes: learning tools, teaching methodologies and evaluation processes; and finally, to describe comparisons of the use of evaluation instruments by our residency program and other experiences in the literature. Methods: Review and analysis of the main international experiences in training of family physicians; conducting a series of workshops and creation of working groups with specific areas, themes and responsibilities for study, presentation and collective definition. Results: Elaboration of a competency curriculum based on a five-dimensional competence model. Conclusion: Establishing a competency-based curriculum is vital to in the organization of the residency program. The use of international and national references and the contribution of the people involved in the residence program favor the organization of competences while respecting the singularities of the residency program. Challenges are encountered in implementing the curriculum in the practice of the day.